Heat stress does not augment ventilatory responses to presyncopal limited lower body negative pressure. Issue 7 (13th May 2013) - Pearson, J.; Ganio, M. S.; Lucas, R. A. I.; Babb, T. G.; Crandall, C. G.
New Findings:   What is the central question of this study? Simulated haemorrhage increases ventilation prior to presyncope, possibly increasing venous return through the respiratory pump. Heat stress alone also increases ventilation. It is unknown whether this increased ventilation would be greater with combined heat stress and simulated haemorrhage.   What is the main finding and its importance? Our data suggest that the increased ventilation during simulated haemorrhage induced via lower body negative pressure is not altered in heat‐stressed humans. These findings have implications for individuals who are often heat stressed and at a higher risk of haemorrhagic injury. During a hypotensive challenge whilst heat stressed, these individuals are unlikely to realize benefits of a heightened respiratory pump relative to when they are normothermic. Simulated haemorrhage, e.g. lower body negative pressure (LBNP), reduces central blood volume and mean arterial pressure, while ventilation increases. Passive whole‐body heat stress likewise increases ventilation. The objective of this project was to test the hypothesis that ventilatory responses to reductions in central blood volume and arterial pressure during simulated haemorrhage are enhanced when individuals are heat stressed rather than normothermic. Eight healthy men (34 ± 9 years old, 176 ± 6 cm tall and 80.2 ± 4.2 kg body weight) underwent a simulated haemorrhagic challenge via LBNP until presyncope on two separate occasions, namely normothermic control and whole‐body heat‐stress trials. Baseline ventilation and core and mean skin temperatures were not different between trials (all P > 0.05). Prior to LBNP, heat stress increased core (from 36.8 ± 0.2 to 38.2 ± 0.2°C, P < 0.05) and mean skin temperatures (from 33.9 ± 0.5 to 38.1 ± 0.6°C, P < 0.05), as well as minute ventilation (from 8.01 ± 2.63 to 13.68 ± 6.68 l min ‐1, P < 0.01). At presyncope, mean arterial pressure and middle cerebral artery blood velocity decreased in both trials ( P < 0.05). At presyncope, ventilation increased to 23.22 ± 6.78 ( P < 0.01) and 25.88 ± 10.16 l min ‐1 ( P < 0.01) in the normothermic and hyperthermic trials, respectively; however, neither the increase in ventilation from the pre‐LBNP period nor the absolute ventilation was different between normothermic and hyperthermic trials ( P > 0.05). These data suggest that the increase in ventilation during simulated haemorrhage induced via LBNP is not altered in heat‐stressed humans.